Etika Profesi Notaris Sebagai Pedoman Moral Dan Instrumen Perlindungan Hukum Dalam Pelaksanaan Jabatan - Emiliana Laku Mali (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2025)
Notaries, as public officials, have strategic authority in creating legal certainty through the creation of authentic deeds. This authority places notaries in a position that is vulnerable to pressure from vested interests and legal risks. Therefore, professional ethics are very important, not only as moral guidelines in carrying out their duties, but also as a legal protection instrument for notaries themselves. This study aims to analyze the role of notary professional ethics as a guideline for performing their duties and as a form of legal protection against civil, criminal, and administrative risks. The research method used is normative legal research with a legislative and conceptual approach. The results of the study show that notary professional ethics function as a moral compass in professional decision-making and as preventive protection against potential legal violations. Compliance with professional ethics strengthens the integrity of the notary position and maintains public trust as the main basis for the existence of the notary profession.